SUSTAINABLE DEVELOPMENT GOALS IN INTERNATIONAL INVESTMENT PROMOTION AND PROTECTION AGREEMENTS - Njegovan, Milica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Sustainable development goals represent the paradigm of international politics of the 21st century. Their importance is also reflected in the growing number of national and international legal sources that directly or indirectly prescribe provisions for their affirmation. The international investment law, as a diverse set of international legal sources traditionally focused on the protection of foreign investments, has been increasingly linked to the requirements for contributing to the sustainable development of the host state. This paper analyzes the provisions of international investment agreements (IIAs) in the context of various aspects of sustainable development. Preambles, substantive and procedural provisions of bilateral and other international agreements containing provisions on investment protection were analyzed. The conclusion is that in the existing corpus of IIAs, still a smaller number of them contain provisions important for sustainable development, but that a trend can be observed of increasingly frequent incorporation of these "modern" provisions into newly signed agreements, as well as into the modern model BITs.
Keywords: sustainable development, international investment law, International investment agreements (IIAs), investment arbitration